Coping with the loss of large, energy‐dense prey: a potential bottleneck for Weddell Seals in the Ross Sea. Issue 1 (4th January 2017) - Salas, Leo; Nur, Nadav; Ainley, David; Burns, Jennifer; Rotella, Jay; Ballard, Grant
Abstract: Extraction of Antarctic toothfish ( Dissostichus mawsoni ) in the Ross Sea began in 1997, following a management plan that targets the largest fish with a goal of reducing the spawning biomass by 50% over 35 yr. We investigate the potential long‐term consequences of the reduced availability of this prey for Weddell seals ( Leptonychotes weddellii ). Energy demands in seals are acute, especially immediately following lactation, when females must recover substantial mass and cope with molting costs. We tested the hypothesis that toothfish are critically important for adult female seals during this period. Toothfish body mass is three orders of magnitude greater, and its energy density nearly double that of the most common seal prey, Antarctic silverfish ( Pleuragramma antarcticum ). Reduction or elimination of toothfish consumption could impair a female's ability to sufficiently recover and successfully produce a pup in the following pupping season. Our goals are to (1) illustrate mechanisms and conditions whereby toothfish depletion might plausibly affect seal population trends; (2) identify measurable parameters of the seals' ecology that may help better understand the potential negative impact of toothfish depletion on seal populations; and (3) promote a precautionary management approach for the fishery that includes monitoring of seal populations We constructed a set of inter‐linked models of seal diving behavior, physiological condition, and demography based on existing information. We evaluate the effect of the following factors on seal mass recovery and intrinsic population growth rates: fishery depletion rate, daily diving limits, probability of a successful dive, and body mass recovery target. We show that loss of toothfish has the greatest potential impact on seal populations' growth rate. Under some scenarios, populations may decrease at >10% per year. Critical parameters to better understand fishery impacts include prevalence and size of toothfish in the seals' diet; the relationship between diet and the rate of mass recovery; and female breeding propensity in relation to body condition at the end of the molting period. Our results lend support to concerns about the potential negative impact of toothfish extraction in the Ross Sea; and to advocate for a precautionary management approach by the fishery.